2022
DOI: 10.3341/kjo.2022.0061
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Netarsudil/Latanoprost Therapy with Latanoprost Monotherapy for Lowering Intraocular Pressure: A Systematic Review and Meta-analysis

Abstract: Netarsudil is a Rho kinase inhibitor and the first new class of clinically useful ocular hypotensive agents. In this study, we conducted a systematic literature review and meta-analysis to summarize and synthesize the available evidence on the efficacy and safety of fixed dose combination (FDC) therapy with netarsudil/latanoprost in patients with glaucoma. Methods:We identified relevant studies in PubMed, Medline, Embase, and Cochrane Central until April 2021. The quality of the studies and the level of eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 36 publications
0
4
0
2
Order By: Relevance
“…In this regard, Tanihara et al, in 2015, found significant additive IOP reduction ranging from 0.9 mmHg (95% CI, 0.4–1.3 mmHg; p < 0.001) to 1.6 mmHg (95% CI, 1.1–2.1 mmHg; p < 0.001) with combined therapy of ripasudil with timolol, compared to timolol alone [ 30 ]. Likewise, Lee et al, in 2022, found a reduction of −2.41 mmHg (95% confidence interval [CI], −2.95 to −1.87) with combined therapy of netarsudil with latanoprost, compared to −1.77 mmHg (95% CI, −2.31 to −1.87) with latanoprost alone [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, Tanihara et al, in 2015, found significant additive IOP reduction ranging from 0.9 mmHg (95% CI, 0.4–1.3 mmHg; p < 0.001) to 1.6 mmHg (95% CI, 1.1–2.1 mmHg; p < 0.001) with combined therapy of ripasudil with timolol, compared to timolol alone [ 30 ]. Likewise, Lee et al, in 2022, found a reduction of −2.41 mmHg (95% confidence interval [CI], −2.95 to −1.87) with combined therapy of netarsudil with latanoprost, compared to −1.77 mmHg (95% CI, −2.31 to −1.87) with latanoprost alone [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…El desarrollo de nuevos tratamientos farmacológicos, como los inhibidores de la rho quinasa, que a través de la vía trabecular promueve el drenaje del humor acuoso. Kahook Las investigaciones realizados para evaluar eficacia corroboraron que el Netarsudil comparado con Latanoprost y Timolol solo puede considerarse de eficacia similar en los pacientes con PIO base de aproximadamente 25-26mmHg, por lo cual puede ser eficaz en casos de PIO con valores bajos (37) En la investigación de Asrani et al (33), se señala que la combinación fija de Netarsudil Latanoprost (FCNL) una vez al día demostró reducciones de la PIO que fueron estadística y clínicamente superiores a Netarsudil y Latanoprost como monoterapia, con una seguridad ocular aceptable.…”
Section: Discussionunclassified
“…Las Reacciones adversas más frecuentes fueron 8.6% blefaritis, 8.5% hiperemia conjuntival, 6.3% conjuntivitis, prurito ocular 1,7%. En la investigación de Asrani et al (33) se señala que la combinación fija de netarsudil-latanoprost (FCNL) una vez al día demostró reducciones de la PIO que fueron estadística y clínicamente superiores a Netarsudil y Latanoprost como monoterapia, con una seguridad ocular aceptable. El efecto adverso más frecuente fue la hiperemia conjuntival 53,4%, a los que se les administró (FCNL) el 41% Netarsudil y el 14% Latanoprost, cornea verticillata en el 5%, en pacientes tratados con (FCNL), 4,1% Netarsudil, pero ninguno tratado con Latanoprost, otros efectos presentados son dolor en el lugar de instalación, prurito ocular y aumento del lagrimeo.…”
Section: Muestra De Pacientes: 3178unclassified
“…Therefore, a combination of netarsudil with latanoprost would be more beneficial than the monotherapy if netarsudil is considered the treatment choice for patients with glaucoma. According to the literature, application of a netarsudil/latanoprost fixed-dose combination once daily appears to be superior to netarsudil or latanoprost monotherapy for IOP reduction in patients with glaucoma [ 37 ]. These advantages of drug combinations emerged when monotherapy was found to be insufficient for some patients.…”
Section: Rock Inhibitors In Clinical Use For Glaucoma Therapymentioning
confidence: 99%
“…These advantages of drug combinations emerged when monotherapy was found to be insufficient for some patients. Nonetheless, conjunctival hyperemia remains a major complication; however, serious adverse reactions were not observed in patients who received a netarsudil/latanoprost fixed-dose combination [ 37 ]. A fixed-dose combination of 0.02% netarsudil/0.005% latanoprost was well tolerated in the management of patients with glaucoma and demonstrated a significant and sustained reduction in IOP, even as a last-line therapy before incisional or laser surgery in patients on maximum glaucoma pharmacotherapy.…”
Section: Rock Inhibitors In Clinical Use For Glaucoma Therapymentioning
confidence: 99%